Representações sociais de professoras sobre o transtorno do déficit de atenção-hiperatividade em uma escola da rede estadual no Pará - MATOS, Bruna Adriely Albuquerque (2020)
This research aims to know the Social Representations (SR) of two groups of teachers of the first period of Elementary School in a State School in the city of Belém, dealing with them on Attention-Hyperactivity Disorder (AHD) in their students, four teachers, two from the common teaching room, and two from the Specialized Educational Service (SES) were contacted to do the research, in order to relate the meanings and meanings presented by them, and to identify pedagogical practices with these students. This work has as methodological basis the Theory of Social Representations (TSR), We have made use of semi-structured interviews within a qualitative approach, the research is divided in a trajectory of four. The construction of the knowledge of various subjects and objects can be done through social representations, based on the authors Nascimento (0000) and Moscovici (1978), RS are generated through the exchange and communication, the use of social representations the analyzes of this research. This way, we visualize that the teachers have social representations about AHD, these are constituted from the shares and their experiences, they conceive that the students with AHD are proactive they can to have a satisfactory intellectual cognitive development, and of course, the students can interact and contribute to their class. However, there are representations rooted in values and beliefs where students with AHD were not seen as capable of developing cognitively, resulting in ineffective pedagogical practices and interventions for student development.